Factors influencing five-year adherence to adjuvant endocrine therapy in breast cancer patients: A systematic review - Izzati Yussof; Nor Asyikin Mohd Tahir; Ernieda Hatah; Noraida Mohamed Shah (Breast, 2022)
Purpose: This systematic review aimed to determine the rate and identify correlates of adherence and persistence over five years of treatment with adjuvant endocrine therapy in female breast cancer patients. Methods: Relevant articles were identified from Medline, Embase, AMED, PsycINFO, International Pharmaceutical Abstracts, and APA PsycArticles. Studies that measured patient adherence in the implementation or persistence phase for a period of at least five years using objective or multiple measures of adherence and investigated correlates of adherence were included. The titles, abstracts and full articles were screened and reviewed by two authors and any discrepancies were discussed with a third author. Results: Twenty-six studies were included. Mean rate of adherence at five-year for implementation phase was 66.2% (SD = 17.3%), and mean persistence was 66.8% (SD = 14.5%). On average, adherence decreased by 25.5% (SD = 9.3%) from the first to fifth year. Higher rate of adherence was observed through self-report in comparison to database or medical record. Older age, younger age, higher comorbidity index, depression and adverse effects were associated with lower adherence. Treatment with aromatase inhibitors, received chemotherapy, and prior medication use were associated with improved adherence. Conclusion: Adherence to adjuvant endocrine therapy decreased from the first to fifth year of treatment. On average, one-third of patients were not adherent to treatment by the fifth year. Nineteen recurring factors were found to be significantly associated with long-term adherence in multiple studies. Further research using objective or multiple measures of adherence are needed to improve validity of results.